Myogenic tone is impaired at low arterial pressure in mice deficient in the low‐voltage‐activated CaV3.1 T‐type Ca2+ channel. (18th February 2013) - Björling, K.; Morita, H.; Olsen, M. F.; Prodan, A.; Hansen, P. B.; Lory, P.; Holstein‐Rathlou, N.‐H.; Jensen, L. J.
Abstract Aim Using mice deficient in the CaV3.1 T‐type Ca2+ channel, the aim of the present study was to elucidate the molecular identity of non‐L‐type channels involved in vascular tone regulation in mesenteric arteries and arterioles. Methods We used immunofluorescence microscopy to localize CaV3.1 channels, patch clamp electrophysiology to test the effects of a putative T‐type channel blocker NNC 55‐0396 on whole‐cell Ca2+ currents, pressure myography and Ca2+ imaging to test diameter and Ca2+ responses of the applied vasoconstrictors, and Q‐PCR to check mRNA expression levels of several Ca2+ handling proteins in wild‐type and CaV3.1−/− mice. Results Our data indicated that CaV3.1 channels are important for the maintenance of myogenic tone at low pressures (40–80 mm Hg), whereas they are not involved in high‐voltage‐activated Ca2+ currents, Ca2+ entry or vasoconstriction to high KCl in mesenteric arteries and arterioles. Furthermore, we show that NNC 55–0396 is not a specific T‐type channel inhibitor, as it potently blocks L‐type and non‐L‐type high‐voltage‐activated Ca2+ currents in mouse mesenteric vascular smooth muscle cell. Conclusion Our data using mice deficient in the CaV3.1 T‐type channel represent new evidence for the involvement of non‐L‐type channels in arteriolar tone regulation. We showed that CaV3.1 channels are important for the myogenic tone at low arterial pressure, which is potentially relevant under resting conditions in vivo. Moreover, CaV3.1 channels are not involved in Ca2+ entry and vasoconstriction to large depolarization with, for example, high KCl. Finally, we caution against using NNC 55–0396 as a specific T‐type channel blocker in native cells expressing high‐voltage‐activated Ca2+ channels.